Photodetachment Studies of Ir− Ions at DESIREE. Issue 13 (January 2020) - Kristiansson, M K; Sundberg, J; Hanstorp, D; Eklund, G; Cederquist, H; Zettergren, H; Schmidt, H T
Synopsis: Anions of iridium were stored in the cryogenic storage ring, DESIREE [1, 2, 3] and investigated using laser photodetachment. The ions were stored for up to 2000 seconds and the relaxation of several metastable states were studied by selecting different photon energies. The threshold of the previously not observed 3 P2 level is located and the lifetime of this sate is found to be longer than the storage time of the ion beam. We also find that a state exists higher in energy than the previously known level with a lifetime in the range of hundreds of milliseconds.